The Arab uprising : the unfinished revolutions of the new Middle East - Lynch, Marc, 1969- (New York : PublicAffairs, 2012)
Will the Arab world's struggle for change succeed in building open societies, or will authoritarian regimes regain their grip? Lynch follows the struggles from Tunisia and Egypt to Yemen, Syria, and Libya, and to the cautious reforms of the region's monarchies, and reveals how America must adjust to the new realities.
Introduction -- The Arab uprisings -- The Arab cold war -- Building toward revolution -- A new hope -- The tidal wave -- The empire strikes back: the counterrevolution -- Intervention and civil war -- America's challenge.
Includes bibliographical references (pages 241-255) and index.
Keywords: Democratization -- Arab countries; Democratization -- Middle East; Democracy -- Arab countries; Democracy -- Middle East; Protest movements -- Arab countries -- History -- 21st century; Protest movements -- Middle East -- History -- 21st century; Protest movements -- Arab countries; Arab countries -- Politics and government -- 21st century; Middle East -- Politics and government -- 21st century